IMPLEMENTASI PENERAPAN PROTOKOL KESEHATAN DI ERA NEW NORMAL PADA PEKERJA DI LOKA PENELITIAN KAMBING POTONG (LPKP) SEI PUTIH KECAMATAN GALANG - Sri Melda Br Bangun; Ade Putri Husniawati; Ika Nur Saputri (JURNAL KESMAS DAN GIZI (JKG), 2021)
At the end of 2019 a new virus was discovered which is now an infectious disease outbreak around the world and WHO (World Health Organization) gives the name of the virus that is currently endemic as Covid-19 (Corona Virus Diseases 2019). This research is a qualitative research that aims to collect in-depth data from sources or informants by conducting direct interviews. The number of informants in this study were 10 people. The data collection is done by direct observation to field conducted in-depth interviews of workers and equipped with recording equipment sound made to 10 informants. The results of the research carried out are that there are workers who have not been able to carry out and implement health protocols in accordance with the recommendations of the government. Of the several health protocols that exist at the Slaughter Goat Research Workshop, there are health protocols that have been violated by workers, namely all workers do not wear masks when in the work environment, the absence of workers who apply physical or social distancing during work or during rest hours, water and hand washing soap are not provided and hand sanitizers are never used and are only for display in the office, and workers believe that it is impossible for fellow workers to transmit the Covid-19 virus to fellow workers although there are already some workers in Loka Penelitian Kambing Potong who have contracted the virus, they are not worried and are not afraid of it. The advice that can be given is that workers must be aware of the importance of implementing health protocols and Loka Penelitian Kambing Potong should provide guidance and direction to workers in an effort to suppress the decline in Covid-19 cases